TINJAUAN DUKUNGAN INFORMASI DARI UNIVERSITAS SEBAGAI FAKTOR PENDORONG MAHASISWA UNTUK MENGIKUTI PROGRAM KREATIVITAS MAHASISWA - Muhammad Subakti; Primawati Primawati; Zainal Abadi; Rizky Ema Wulansari (Unversitas Negeri Padang, 2024)
The Student Creativity Program (PKM) is initiated by Dikjen Diktirestik through Belmawa to fulfill one of the 8 Key Performance Indicators (IKU) of Higher Education, focusing on graduates' success in securing suitable employment and providing students with off-campus experiences. The Department of Mechanical Engineering at FT-UNP actively participates in PKM each year. Therefore, this study aims to thoroughly examine the influence of University Information Support as a catalyst for the participation of Mechanical Engineering students in PKM. The research employs a quantitative approach involving 282 Mechanical Engineering students, validating instruments and collecting data. Data analysis is conducted researchers utilized the SmartPLS application for conducting Structural Equation Modeling (SEM) in their study. Findings reveal that University Information Support has a significant positive impact on student participation in PKM at the FT-UNP Mechanical Engineering Department, indicated by a Path Coefficient 0.189, T statistics 2.621, and P values 0.009. University Information Support is crucial in enhancing student involvement in the Student Creativity Program, underscoring the importance of adequate information provision by universities.